Guided Discovery Learning-Based Chemistry E-Module and Its Effect on Students' Higher-Order Thinking Skills - Yerimadesi, Y.; Warlinda, Y. A.; Rosanna, D. L.; Sakinah, M.; Putri, E. J.; Guspatni, G.; Andromeda, A. (Jurnal Pendidikan IPA Indonesia, 2023)
This study aims to analyze the effectiveness of guided discovery learning-based e-modules in improving senior high school students' higher-order thinking skills. It belongs to quasi-experimental research with a nonrandomized control-group pretest-posttest design. Three schools in Padang, Indonesia, were chosen as the samples through a purposive sampling technique, and experimental and control classes in each school were assigned based on the homogeneity of their previous academic score. Research instruments were a higher-order thinking cognitive test using multiple-choice questions and worksheets in the guided discovery learning-based e-module made for salt hydrolysis, electrolyte and nonelectrolyte solutions, and chemical elements. Students' test scores were analyzed using the N-gain test and independent sample t-test. The results show that students' higher-order thinking skills in the experimental classes were significantly higher than in the control classes. Most students could fill in the worksheets in the e-modules whose problems were made according to higher-order thinking skills criteria. Multiple representations integrated with learning materials in the e-modules helped students understand chemistry concepts. The ordered stages of guided discovery learning integrated with complete and interactive multimedia in the e-modules facilitated students to engage in learning, investigating, and evaluating information to conclude; the attempts to train higher-order thinking skills. Therefore, it can be concluded that guided discovery learning-based chemistry e-module can effectively improve senior high school students' higher-order thinking skills.